2012
DOI: 10.1007/s10689-012-9512-z
|View full text |Cite
|
Sign up to set email alerts
|

French women’s breast self-examination practices with time after undergoing BRCA1/2 genetic testing

Abstract: To assess the impact of BRCA1/2 genetic test results on cancer-free women's breast-self-examination (BSE) practices and to prospectively determine their influence on psychological functioning. A prospective longitudinal study on French women's BSE practices and frequencies in BRCA1/2 carriers (N = 217) and non-carriers (N = 313) 1 and 2 years following disclosure of the test results, along with psychological factors predicting BSE practices. Before disclosure, BSE was practised by 47.2% of the women, and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…It is worth emphasising that the increase of the frequency of performing self-examination after conducting the genetic test was not related to the level of education. 14 An attempt was made to show the correlation between the level of education and the effects of training in breast self-examination in a study involving 413 Turkish women aged 20-59. The results of the study showed that the Turkish women, regardless of the level of education, need support in this area -both informative and instrumental.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth emphasising that the increase of the frequency of performing self-examination after conducting the genetic test was not related to the level of education. 14 An attempt was made to show the correlation between the level of education and the effects of training in breast self-examination in a study involving 413 Turkish women aged 20-59. The results of the study showed that the Turkish women, regardless of the level of education, need support in this area -both informative and instrumental.…”
Section: Discussionmentioning
confidence: 99%
“…In women, age has been shown to have a significant impact on cancer risk due to its association with risk‐reducing behaviors . Interventions to reduce cancer risk in mutation‐carrying patients include the following: earlier, more frequent, or more intensive cancer screening; risk‐reducing treatment; and risk‐reducing surgery, including bilateral mastectomy and salpingo‐oophorectomy . Men can also carry a BRCA1/2 mutation, but the implications for them are less clear because they appear to have different motivations for undergoing genetic counseling.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on the French Gene Etude Prospective Sein Ovaire PsychoSocial (GENEPSO‐PS) cohort, which was derived from the GENEPSO cohort created in 2008 to identify the psychosocial characteristics and preventive behaviors of patients with a BRCA1/2 mutation . After 10 years of follow‐up, we decided to study the children of BRCA1/2 mutation carriers on the assumption that they have an increased risk of developing cancer and that they can therefore benefit from BRCA1/2 genetic testing .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged clinical distress is uncommon after single-gene testing for HBOC susceptibility 19. However, an inconclusive result such as a VUS may elicit misunderstanding,20 21 uncertainty21 22 and decisional conflicts about clinical management,23 potentially leading to increased distress,24 miscommunication between family members25 and inadequate cancer risk management decisions 21 26 27. On receiving a pathogenic moderate-penetrance gene variant, counselees may experience higher distress and uncertainty compared with a negative, VUS and even a pathogenic high-penetrance variant 28…”
Section: Introductionmentioning
confidence: 99%